Lexical and Cultural Nuances in Arabic–Indonesian Translation: Strategies for Novice Translators - Asmilia, Dera; Yul, Widiya; Andrian, Riko (Study Program of Arabic Language Teaching, 2025)
This study explores the lexical and cultural challenges faced by novice translators in Arabic–Indonesian translation, a field that remains relatively underexplored despite its significant pedagogical relevance. The primary aim of this research is to identify common types of translation difficulties and to analyze the strategies employed by novice translators to address them. Utilizing a qualitative case study approach, data were collected from 15 fifth-semester students of the Arabic Language Education Program at the State Islamic Institute (IAIN) of Kerinci, who were enrolled in a translation course. Data were gathered through translation tasks, reflective journals, and semi-structured interviews. Thematic analysis was employed to identify recurring patterns of difficulties and strategies consistently observed during the translation process. The analysis revealed that major translation difficulties stemmed from the morphological complexity of Arabic, syntactic differences, semantic ambiguity, and cultural-linguistic gaps between Arabic and Indonesian. Three key patterns of difficulty were identified: misinterpretation of polysemous words, literal translation of idiomatic expressions, and loss of cultural meaning in context-bound terms. While most participants relied on literal translation and simplification strategies, they generally lacked adequate strategic awareness. Based on these findings, the study proposes a learner-centered contextual strategy model integrating explicit grammar instruction, contrastive Arabic–Indonesian analysis, and meaning-based scaffolding. This model is designed to support novice translators in producing more accurate, context-sensitive, and culturally appropriate translations. The study contributes to the pedagogical development of Arabic–Indonesian translation studies by highlighting learner needs and offering practical solutions relevant to the early stages of language acquisition.